Vitamin D level and hormonal status association in adolescent girls with oligomenorrhea - V.O. Dynnik; O.O. Dynnik; A.Y. Druzhynina (Publishing House TRILIST, 2021)
Research objective: to determine the frequency of vitamin D deficiency and insufficiency to identify its association with reproductive hormones in adolescent girls with oligomenorrhea. Materials and methods. The work was carried out according to the results of clinical and instrumental examination of 68 adolescent girls 12-18 years old with oligomenorrhea, who were treated at the Department of Pediatric Gynecology of the State Institution "Institute for Children and Adolescents Health Care of the NAMS of Ukraine". Patients were divided into two groups depending on the body mass index (BMI): group I - with a body weight deficit (BMI 16.31 ± 0.18 kg/m2), group II - with a BMI within physiological norm (20.0 ± 0.25 kg/m2). All patients underwent a comprehensive clinical and laboratory examination: luteinizing, follicle-stimulating hormones, prolactin, estradiol, testosterone, cortisol, 25(OH)D were determined in blood serum. Multivariate regression analysis was using for analyze the association of gonаdotropic, steroid hormones with vitamin D. The main characteristics of the object discrimination model are presented in the form of tables. Results. The article provides a comparative analysis of the hormonal profile and vitamin D level depending on BMI. It was revealed that a reduced 25(OH)D value was characteristic not only in patients with menstrual dysfunction, but also in peers with normal menstrual function. Schemes that characterize the pituitary-gonadal association with vitamin D were constructed based on the results of multiple regression analysis. Their features were determined in girls with different body weights. In patients with low energy resources there were direct associations between individual indicators of gonadotropins (follicle-stimulating hormone), steroid hormones (estradiol, cortisol) and vitamin D. An inverse association was observed between vitamin D and cortisol and prolactin in girls with balanced energy status. Conclusions. The reduced content of vitamin D is characteristically for patients with menstrual dysfunctions by the type of oligomenorrhea. Associations of gonadotropic, steroid hormones and vitamin D, depending on the energy status (nutrition) of patients with oligomenorrhea were revealed.